Family characteristics as risk factors of stunting among children age 12-59 month - Khairani, Nurul; Effendi, Santoso Ujang (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2019)
Stunting in children (low height for age) increases morbidity  and  mortality rate. It can lead  to poor intelligence and  productivity, and degenerative diseases. The objective  of this research was to investigate the associations of  family characteristics with stunting in  children aged 12-59 months  who visited  the integrated health posts in Ratu Samban District, Bengkulu City.  The hypothesis of  this research was there were associations of family characteristics with stunting in children  aged 12-59 months who visited the integrated health posts in Ratu Samban District, Bengkulu City. This research was conducted in June, 2017. The type of the research was Analytical Survey and the design was Cross Sectional. The subject was mothers  of  children  aged 12-59 months who visited the  integrated health posts in Ratu Samban District, Bengkulu City. The sampling technique was Accidental Sampling and the sample number was 102 mothers. The data were collected by questionnaires and anthropometric assessment. Chi-Square test was used to assess the associations of  family characteristics with stunting. The result showed that  of 102 mothers, 32 mothers (31,37 percent) had  stunted children. Family characteristics (maternal height (p=0.257), maternal education (p=0.455), paternal education (p=0.250), total of family member (p=0.245), and income of family head (p=0.320) were  not associated  with stunting and maternal knowledge (p=0.003) was associated  with stunting. The researchers suggest to the community health center and the integrated health post can conduct nutrition education, and especially about stunting more intensively to increase the knowledge of productive woman, pregnant woman, and mother of children.